2019
DOI: 10.1002/ange.201905075
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Crystal of a Hydrogen‐Bonded Organic Framework Induced by the Collective Molecular Motion of a Twisted π System

Abstract: There is alimited number of reports on mechanically responsive molecular crystals,i ncluding thermo-responsive and light-responsive crystals.Rigid ordered molecular crystals with aclose-packing structure are less able to accept distortion, which hampers the development of such molecular crystals. The thermosalient effect, or "crystal jumping", refers to athermo-responsive system that converts heat into mechanical force by thermally induced phase transition. While they have recently attracted attention as poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…As shown in Figure b, BPMCz-P1 exhibited comparatively low N 2 adsorption, with uptakes of about 35.5 cm 3 /g (1.58 mmol/g) at 77 K. In contrast, BPMCz-P1 scarcely adsorbed N 2 at 273 and 298 K. This is possibly due to the strong interaction between the narrow channel window and nitrogen that hinders gas diffusion into the material, which is a common phenomenon in the research field of HOFs . Interestingly, it showed a comparatively high CO 2 uptake of 57.5 cm 3 /g (2.57 mmol/g) at 273 K. The CO 2 uptake amount of BPMCz-P1 is relatively higher than those of some reported HOFs, such as HOF-11a (30.5 cm 3 /g) and HOF-1 (19.8 cm 3 /g) . The calculated Brunauer–Emmett–Teller (BET) surface area based on the isotherm of CO 2 at 196 K is 146.3 m 2 /g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure b, BPMCz-P1 exhibited comparatively low N 2 adsorption, with uptakes of about 35.5 cm 3 /g (1.58 mmol/g) at 77 K. In contrast, BPMCz-P1 scarcely adsorbed N 2 at 273 and 298 K. This is possibly due to the strong interaction between the narrow channel window and nitrogen that hinders gas diffusion into the material, which is a common phenomenon in the research field of HOFs . Interestingly, it showed a comparatively high CO 2 uptake of 57.5 cm 3 /g (2.57 mmol/g) at 273 K. The CO 2 uptake amount of BPMCz-P1 is relatively higher than those of some reported HOFs, such as HOF-11a (30.5 cm 3 /g) and HOF-1 (19.8 cm 3 /g) . The calculated Brunauer–Emmett–Teller (BET) surface area based on the isotherm of CO 2 at 196 K is 146.3 m 2 /g.…”
Section: Resultsmentioning
confidence: 99%
“…45 Interestingly, it showed a comparatively high CO 2 uptake of 57.5 cm 3 /g (2.57 mmol/g) at 273 K. The CO 2 uptake amount of BPMCz-P1 is relatively higher than those of some reported HOFs, such as HOF-11a (30.5 cm 3 /g) 46 and HOF-1 (19.8 cm 3 /g). 47 The calculated Brunauer−Emmett−Teller (BET) surface area based on the isotherm of CO 2 at 196 K is 146.3 m 2 /g. The sorption isotherms showed a typical type-I isotherm with a very sharp uptake at a low pressure, indicating its microporous nature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, we used a Pd(0)-catalyzed coupling reaction 32 to obtain desired material 1 in moderate yield. The syntheses of 2 and 3 were started from the tetra [2,3]thienylene tetracarboxylic acid (5) 21 and tetrabromotetra [2,3]thienylene (6). 28 The typical amidation of 5 via the corresponding acid chloride and Suzuki coupling of 6 with 7 gave 2 and 3, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…14 For example, the rotation and flipping motion of molecule/functional groups have been used to create materials with ferroelectric, 15−18 temperature-dependent fluorescent 19 and thermodynamic actuation properties. 20,21 While these materials have been developed mainly in the relatively static solid or liquid crystalline phase with several regularities of the molecular assemblies, such liquid materials could also be created with an appropriate molecular design. In this work, we focused on liquid COT derivatives for this purpose.…”
Section: ■ Introductionmentioning
confidence: 99%
“…HOF JLU-SOF-1-R composed of the homochiral 11 had an SA (BET) value of 460 m 2 g − 1 and selective sorption toward CO 2 [81]. Takeda et al demonstrated that twisted cyclic tetrathienylene 12 yielded a jumping HOF [82]. Stoddart et al reported that triptycene derivative 13a and 13b provided interpenetration polymorphs of H-bonded networks [83,84].…”
Section: Networked Structures Connected By Carboxylic Acid Dimersmentioning
confidence: 99%